Associations between the exposure to persistent organic pollutants and type 2 diabetes in East China: A case-control study. (February 2020) - Han, Xu; Meng, Lingling; Li, Yingming; Li, An; Turyk, Mary E.; Yang, Ruiqiang; Wang, Pu; Xiao, Ke; Zhao, Junpeng; Zhang, Jianqing; Zhang, Qinghua; Jiang, Guibin
Abstract: Persistent organic pollutants (POPs) have been associated with a high risk of type 2 diabetes in different regions, although few studies from China have been published. We aimed to investigate the associations between POP exposure and type 2 diabetes in Chinese population. A total of 158 participants diagnosed with type 2 diabetes and 158 participants without the disorder from Shandong Province were enrolled in this case-control study during 2016–2017. Nine polychlorinated biphenyl congeners (PCBs) and 2 polybrominated diphenyl ethers with detectable levels in ≥75% of the participants were selected for data analysis. The results showed that POP exposure was significantly and positively associated with the risk of diabetes after adjusting for age, sex, BMI, triglycerides and total cholesterol. However, we did not observe an obvious modified effect of adiposity on the associations between POP exposure and diabetes in the present study, as strong associations between POPs and diabetes were observed in both the higher-BMI (BMI≥25 kg/m 2 ) and the lower-BMI (BMI<25 kg/m 2 ) groups. POPs showed stronger associations with diabetes in males than in females. The odds ratio (OR) for the highest quartile of ∑POPs was 6.97 for males, nearly two times higher than that for females (OR = 3.58). All these findings suggest that POP exposure may impact the risk of diabetes in Chinese population. Highlights: Exposure to PCBs and PBDEs were positively associated with type 2 diabetes. POPs showed stronger associations with diabetes in males than in females. Adiposity did not modify the associations between POPs and diabetes.